Peran Kompensasi dalam Meningkatkan Kinerja Tim di Perusahaan Umum Perkebunan Kahyangan Jember yang Kompetitif - Ilma Masturia; Ulfiatun Nadiroh; Vita Dwi Lestari; Ahmad Wasil Maulidi; Nurul Setiangrum (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the role of the compensation system in improving team performance in a competitive work environment, with a focus on the Public Company of the Kahyangan Jember Plantation Region. In this context, the research used a qualitative approach through semi-structured interviews, group discussions and direct observation to explore the views of employees and managers regarding the existing compensation system. The results of the study show that most employees feel that the compensation system implemented is fair and transparent enough which contributes to improved morale and team performance. Team achievement-based incentives have been proven to encourage collaboration and responsibility among team members. Nonetheless, there is still room for improvement, such as adding bonuses for teams that reach certain targets. The study concludes that the design of an effective compensation system is essential to achieve a productive and harmonious work environment, and provides recommendations for organizations to continuously evaluate and refine existing compensation structures.